Efektivitas Instalasi Pengolahan Air Limbah Industri Gula PG. Pesantren Baru di Kediri Jawa Timur - Benny Edo Prasetyo; Ana Komari; Lolyka Dewi Indrasari (JURMATIS (Jurnal Manajemen Teknologi dan Teknik Industri), 2020)
Sugar Industry PG. Pesantren Baru in treating wastewater produced by production activities using the Waste Water Treatment Plant. The purpose of this study is to determine the effectiveness of wastewater treatment plants. The method used in this research is descriptive observational. This research uses primary data obtained from interviews and temporary observations of secondary data from the processing section in the form of inlet and outlet laboratory test results. The parameters of the results of laboratory test analysis. The results of this study were an average pH concentration of 7. The order of decrease in the concentration of these parameters included, 28.15%; 24.43%; 57.90%; 02.58%; 12.35%. But the most effective way to reduce concentration is on the TSS parameter of 57.90%. The results of the evaluation with Wastewater Quality Standards (BML) indicate that all the tested parameters derived from liquid waste are in accordance with those stipulated by the East Java Governor's Regulation. In addition, when compared with Minister of Environment Regulation No. 5 of 2014 concerning Wastewater Quality Standards, the quality of treated wastewater is also in accordance with what has been stipulated in the regulations.Industri Gula PG. Pesantren Baru dalam mengolah limbah cair hasil kegiatan produksi dengan menggunalan Instalasi Pengolahan Air Limbah. Tujuan dari penelitian ini adalah untuk mengetahui efektivitas instalasi pengolahan air limbah. Metode yang digunakan dalam penelitian ini adalah deskriptif observasional.Penelitian ini menggunakan data primer diperoleh dari wawancara dan observasi sementara data sekunder dari bagian pengolahan yang berupa hasil uji laboratorium inlet dan outlet. Parameter hasil analisis uji laboratorium. Hasil penelitian ini adalah konsentrasi pH rata-rata 7. Pengurutan yang dapat diteliti dengan hasil sebagai berikut : 28,15%; 24,43%; 57,90%; 02,58%; 12,35%. Namun yang paling efektif dalam menurunkan konsentrasi adalah pada parameter TSS sebesar 57,90%.PenelitianÂ  yang sudah dilakukan oleh aturan yang ditetapkan Gubernur Jawa Timurberkaitan dengan Peraturan Menteri Lingkungan Hidup yang bernomor 5 pada tahun 2014 berkaitan dengan Baku Mutu Air Limbah sudah sesuai dengan aturan tersebut.